Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan anak Usia Sekolah dasar Tentang Pentingnya Hidrasi: Effectivenness Health Education on Knowledge for Children Elementary School-Age About the Importance of Hydration - Putria Carolina; Takesi Arisandy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Hydration is a state of the body with sufficient fluids to ensure the function of cell metabolism to run optimally in both adults and even children. Children need more water per kilogram of body weight than adults. This is because children have a relatively larger body surface area, the immature function of urine concentration by the kidneys, and a faster respiratory rate. The phenomenon that often occurs in children is lack of fluids which can have an impact on decreasing concentration while studying and even being sick. Lack of knowledge and awareness is one of the predisposing factors for children to experience problems meeting fluid needs. Through health education it is hoped that it can increase children's knowledge of the importance of hydration to meet fluid needs, with good knowledge. The research design uses quantitative methods with the type of Pre-Experimental research using the One group pre-post test design approach. Data collection measuring instrument questionnaire, data were analyzed using the Wilcoxon statistical test. The research results show a significant p value Asmp. Sig. (2 tailed) of 0.034. It was found that there was an effect of health education on elementary school-age children's knowledge about the importance of hydration. The results of this study can be used as an intervention in child nursing care to improve the quality of nursing services in clinical and community settings. Along with increased knowledge, it will change behavior for the better to achieve optimal child health status.